Influencing factors of hospital-acquired COVID-19 prevention and control status among emergency support frontline healthcare workers under closed-loop management: a cross-sectional study - Luo, Man; Xia, Guoqin; Gan, Tieer; Zhao, Zhifang; Wu, Jiannong; Hu, Ting; Wang, Lucong; Zhang, Yiyin (Frontiers in Public Health, 2023)
Background This study aimed to understand the hospital-acquired COVID-19 infection rate and infection prevention and control status of emergency support frontline healthcare workers (ESFHCWs) under closed-loop management, and to explore the related factors affecting hospital-acquired COVID-19 prevention and control status. Methods The study site was a provincial-level tertiary hospital in the Xinjiang Uygur Autonomous Region specializing in treating COVID-19 patients. ESFHCWs were assigned from different hospitals in Zhejiang Province to provide emergency medical support in this specialized hospital. All ESFHCWs were managed using a closed loop. A self-designed questionnaire was used to estimate basic information, work experience, and the status of infection prevention and control (SIPC). A total of 269 ESFHCWs responded to the questionnaire. A generalized linear regression model was used to estimate the factors influencing SIPC. Results There were six hospital-acquired COVID-19 cases, with an infection rate of 2.23%. The independent risk factors influencing COVID-19 prevention and control status were work seniority, anxiety disorder, and consumption of gastrointestinal, anti-inflammatory and anti-asthmatic, and hypnotic sedative drugs. Compared with ESFHCWs with more than 10 years of work seniority, ESFHCWs with less than 5 years of work seniority and 5–10 years of work seniority had lower COVID-19 SIPC scores. Among ESFHCWs with anxiety disorder, the SIPC score was significantly lower than that of ESFHCWs without anxiety disorder. The SIPC scores of ESFHCWs taking other medications (gastrointestinal, anti-inflammatory and anti-asthmatic, and hypnotic sedative drugs) were lower than those of ESFHCWs who did not. Conclusion The closed-loop management method may be effective in reducing the infection rate of hospital-acquired COVID-19 among ESFHCWs. HCWs with less than 10 years of work seniority, anxiety disorder, and other medications (gastrointestinal, anti-inflammatory and anti-asthmatic, and hypnotic sedative drugs) were probably not suitable for participating in emergency assistant actions because of their poor SIPC scores. Further studies are needed to develop the selection criteria for ESFHCWs.